The Premonition Code: The Science of Precognition by Theresa Cheung and Julia Mossbridge - Katz, Debra Lynne (Journal of Scientific Exploration, 2019)
The Premonition Code is a warm, thought-provoking, introductory book for non-academic readers who are seeking to understand, explore and even expand their own precognitive experiences. Its strength lies in the rich and moving anecdotal stories told by people from all walks of life, including several scientists, whose accounts of precognitive dreams and waking premonitions will certainly be familiar and comforting to those who have had similar experiences and felt alone, or even questioned their own sanity. The Premonition Code is co-authored by Dr. Julia Mossbridge and Theresa Cheung. Mossbridge holds a doctorate in Communication Sciences and Disorders from Northwestern University and an MA in Neuroscience from the University of California at San Francisco. She is an Associate Professor in Integral and Transpersonal Psychology at the California Institute of Integral Studies and a Research Fellow at the Institute of Noetic Sciences. She is a co-author of Transcendent Mind: Rethinking the Science of Consciousness. Mossbridge has personally had precognitive dreams and other exceptional experiences throughout her life, and has recently begun studying remote viewing. Theresa Cheung holds a Master’s degree in Theology and English from Kings College, Cambridge. She has authored close to a dozen popular books, including metaphysical “encyclopedias” and collections of stories about topics such as life after death, the angelic realm, and visitations from deceased loved ones. While Cheung comes from a long line of psychics and spiritualists, she states within the present book that she only recently became aware that formal research existed on extrasensory perception and precognition. The Premonition Code provides a precursory exploration of mind bending questions such as does the future influence the past? Can the future be changed through will and intent in the present? What actually is time? Why do some aspects of premonitions seem to play out and not others? And what to do if someone has had a dream or vision of an impending disaster or a crime? At the core of the book is the contention that readers should embrace their innate intuitive abilities by choosing to become a “positive precog,” defined as a person who seeks to develop and utilize precognition for the betterment of their own life, and that of others. The authors offer their own “positive precog principles” using the acronym REACH, which stands for: Respect for the unknown, Ethics, Accuracy, Compassion, and Honesty (p. 80).